Studi Pemanfaatan Ruang Publik pada Komentar “Opini Anda” di RRI Pontianak - Redatin Parwadi (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2005)
This research aimed to investigate the use of public segment and audiences’ mapping of program Kopi Anda or Your Opinion Comment at RRI Pontianak. The research result showed that community’s response towards Your Opinion Comments segment at RRI Pontianak was highly positive. During a six-month research, the number of responses was reaching no less than 230 peoples, consisting of 200 males and 30 famales. There was 178 topics aired interactively and obtained 1.744 responses. On average, a topic was responded by 8 to 13 responses. The most favorite topic was politic (especially those which dealing with government administration). Mostly responses were addressed to executive officers and legislative members. Although the people were enthusiastically in participating to provide suggestion, inputs, and criticisms on the public policy, in terms of provincial or district/municipality, but responses requiring time, fund, and ideas from the people were rarely being cared. One possible reason for such problems derived for the fact that the officers and legislative members have never listened to the radio, despite the power of radio as communication media—therefore, as mediator—between people and their government as well as their representatives in regional legislative institution.